Central Bank Independence : Issues and Experience. (IMF Working Papers; Working Paper ;, 1991)
There has been growing interest recently in the scope for promoting monetary stability through the establishment of independent central banks. This paper reviews the issues involved in central bank independence against the background of arrangements in nine countries. The analysis suggests that detailed institutional arrangements would need to be carefully designed if the potential benefits of central bank independence are to be delivered. Particularly important are the nature of arrangements to resolve various types of conflicts involving monetary policy, and arrangements to promote accountability and public monitoring of monetary policy performance.